2014
DOI: 10.1111/jcpp.12320
|View full text |Cite
|
Sign up to set email alerts
|

Practitioner Review: Effective ingredients of prevention programs for youth at risk of persistent juvenile delinquency – recommendations for clinical practice

Abstract: Prevention programs have positive effects on preventing persistent juvenile delinquency. In order to improve program effectiveness, interventions should be behavioral-oriented, delivered in a family or multimodal format, and the intensity of the program should be matched to the level of risk of the juvenile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
55
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 94 publications
(100 reference statements)
12
55
2
Order By: Relevance
“…Thus, it seems of the utmost importance that the national health system, schools, and child protection services become able to identify, assess, and/or intervene effectively with at-risk children in early stages of the development. This kind of preventive policy has proven to have positive effects on preventing persistent juvenile delinquency, namely when interventions are behavioral-oriented, delivered in a family or multimodal format, and when their intensity matches the level of risk presented by the juveniles [42]. Secondly, though most young offenders either placed in juvenile detention facilities or receiving community-based programs present disruptive disorders and/or antisocial personality disorder, results highlight a considerable variability in the psychiatric symptomatology of these youth.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it seems of the utmost importance that the national health system, schools, and child protection services become able to identify, assess, and/or intervene effectively with at-risk children in early stages of the development. This kind of preventive policy has proven to have positive effects on preventing persistent juvenile delinquency, namely when interventions are behavioral-oriented, delivered in a family or multimodal format, and when their intensity matches the level of risk presented by the juveniles [42]. Secondly, though most young offenders either placed in juvenile detention facilities or receiving community-based programs present disruptive disorders and/or antisocial personality disorder, results highlight a considerable variability in the psychiatric symptomatology of these youth.…”
Section: Discussionmentioning
confidence: 99%
“…showed that the average case treated with family therapy fared better than 58–59 per cent of cases who engaged in treatment as usual or alternative treatments in terms of a range of outcomes including recidivism, antisocial behaviour, drug use, scholastic achievement, family functioning, and deviant peer group contact. These results are consistent with those of other systematic reviews and meta‐analyses of studies of systemic interventions for conduct problems (de Vries et al ., ; Dowden and Andrews, ; Latimer, ; Woolfenden et al ., ) and substance misuse (Austin et al ., ; Becker and Curry, ; Rowe, ; Vaughn and Howard, ; Waldron and Turner, ).…”
Section: Conduct Problemsmentioning
confidence: 99%
“…Following De Vries et al. (), the following designations were used in coding the primary format of the included programs. The individual format ( n = 4, 14.8%, k = 6) included programs that delivered services directly to youth (i.e., youth individual counseling; individual mentoring; case management).…”
Section: Methodsmentioning
confidence: 99%
“…While the juvenile legal system has traditionally focused its efforts on treating youth upon their entry into the system, more recently the system has shifted to a proactive and preventive approach (OJJDP, ). Research has shown that both prevention and selected/indicated programs for youth DBP result in positive, small to moderately sized effects (i.e., De Vries et al., ; Wilson & Lipsey, ). With regard to differential effects by treatment type, a meta‐analysis demonstrated support for programs that aim to change youth's individual cognitions and behaviors (ф = .12–.13; Lipsey, ), but the potential effect based on gender has not been examined.…”
Section: Introductionmentioning
confidence: 99%